2016
DOI: 10.1186/s12906-016-1476-3
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum beta 1,3/1,6 glucan as an immunomodulator in inflammation induced by a high-cholesterol diet

Abstract: BackgroundBinding of beta 1,3/1,6 glucan of Ganoderma lucidum (G. lucidum) with the receptor results in a series of signal transfers (signalling cascades), which activates the transcription factors for regulating inflammation. Excess cholesterol intake leads to an increase in the distance between fat cells and capillaries, which may cause hypoxia in the fat tissue of obese mice. This hypoxia induces the death of fat cells, resulting in the inflammation of adipose tissue or an increase in the inflammatory gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Nevertheless, if one considers that it did not reveal any significant effect on blood pressure and could also exert a toxic effect on platelets and other cellular blood components, its use in CVD prevention can be excluded. Yet, this by no means discredits the immunomodulatory and potential anticancer activities of polysaccharides such as the water-soluble 1,3-β-and 1,6-β-glucans isolated from G. lucidum [58,59]. The cytotoxic effect observed in the present study should be attributed to the triterpenoids, which are broadly represented in G. lucidum fruiting bodies.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, if one considers that it did not reveal any significant effect on blood pressure and could also exert a toxic effect on platelets and other cellular blood components, its use in CVD prevention can be excluded. Yet, this by no means discredits the immunomodulatory and potential anticancer activities of polysaccharides such as the water-soluble 1,3-β-and 1,6-β-glucans isolated from G. lucidum [58,59]. The cytotoxic effect observed in the present study should be attributed to the triterpenoids, which are broadly represented in G. lucidum fruiting bodies.…”
Section: Discussionmentioning
confidence: 56%
“…G. lucidum polysaccharides also protect fibroblasts against UVB-induced photoaging [ 15 ]. G. lucidum also showed strong anti-inflammatory activity and it acted as an immunomodulator in inflammation induced by a high-cholesterol diet [ 16 ]. The recent advancement in research has shown the link between gut microbiota and treatment of various ailments.…”
Section: Medicinal Properties Of Mushroommentioning
confidence: 99%
“…Previous studies on a hamster model of hypercholesterolemia using β-glucans isolated from oat and barley also identified that they induce beneficial hypolipidemic and anti-atherosclerotic effects ( 128 , 129 ). Another study found that β-glucan treatment reduced the inflammation induced by a diet high in cholesterol ( 130 ). In a rat experimental model, β-glucans reduced total cholesterol, triglyceride and malondialdehyde levels by 42% ( 131 ).…”
Section: Animal Studiesmentioning
confidence: 99%